Exploring the Guiding Philosophy of the School Administrators in BARMM, Southern Philippines: Responses from the Field - Jupuri A. Madjid (HM Publisher, 2022)
This study aimed at investigating the educational philosophies as applied in the elementary school districts in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), Philippines. Specifically, this papers explored the mission and vision of the school administrators; the application of which western philosophies in the school districts; and the integration of some Islamic practices in the context of the Muslim region. This also included the current administrative programs to achieve the school vision and the needed policy reforms to address some recurring challenges facing the elementary school now-a-days. Meanwhile, in spite of the guiding philosophies embedded in elementary schools, majority of the school administrators have integrated some Islamic philosophies into the context of administering the school. It was also found to have some major programs and policy reforms to improve the school organizational operation.